Architecture History, Theory and Preservation : Prehistory to the Middle Ages - Pabón-Charneco, Arleen (Taylor & Francis Group, 2020)
Cover -- Half Title -- Endorsement -- Title Page -- Copyright Page -- Dedication -- Table of Contents -- Acknowledgements -- Introduction -- Owning the Unknown -- From the Dawn of Time to the Ages in the Middle -- Notes -- Selected Sources -- Chapter 1 A Fixed Place Under the Sky: The Invention of Architecture -- Grasping the Shadow: Theoretical Considerations -- Preserving Prehistory -- Notes -- Selected Sources -- Chapter 2 Out of the Cave: Neolithic Architecture -- Earthwork Architecture -- Megalithic Architecture -- The Urban Center -- Theoretical Considerations -- Conservation Treatments -- Notes -- Selected Sources -- Chapter 3 Rivers of Culture: Mesopotamian and Egyptian Architecture -- Mesopotamian Architecture -- Egyptian Architecture -- Theoretical Considerations -- Conservation Considerations -- Notes -- Selected Sources -- Chapter 4 When the Gods Were Human: Minoan and Mycenaean Architecture -- Minoan Architecture -- Mycenaean Architecture -- Theoretical Considerations -- Conservation Reflections -- Selected Sources -- Chapter 5 Frogs Around a Pond: Architecture in Ancient Greece -- The Architectural Orders -- Acropolis, Temenos and Agora -- The Temple -- Architectural Periods -- The City -- Theoretical Considerations -- Conservation Considerations -- Notes -- Selected Sources -- Chapter 6 In the Tuscan Manner: Etruscan Architecture -- The Urban Defense -- The Etruscan Temple -- Funeral Architecture -- The Tuscan Architectural Order -- Theoretical Considerations -- Preserving Etruscan Architecture -- Note -- Selected Sources -- Chapter 7 As Many Stars as in the Sky: Roman Architecture -- Urban Principles -- The Construction Basics -- The Architectural Orders -- Roman Architecture -- Theoretical Considerations -- Preserving Roman Architecture -- Notes -- Selected Sources.